Theoretical study of acidity of dicarbacloso-dodecaboranes(12) and their chloroderivatives - S. Р. Knyazev; E. G. Gordeev; E. A. Chernyshev (Тонкие химические технологии, 2008)
Quantum-chemical calculation of o-, m-, p-carboranes(12) and C2H2B10Cl10 has been carried out by RHF, DFT(B3LYP) and MP2 methods (6-31G** and 6-311++G**). The analysis of electronic structure of these molecules has been performed. The correlations between electronic and thermodynamic parameters with C-H acidity have been elucidated